Hubungan antara dukungan keluarga dan kualitas Hidup pasien diabetes mellitus tipe ii Di rsud arifin achmad provinsi riau - Ervy - Tamara; Bayhakky - -; Fathra Annis Nauli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The aim of this research was to identify correlation between family support and quality of life of patients with type 2 Diabetes Mellitus in Arifin Achmad General Hospital of Riau Province. The design of the study was correlation with cross sectional approach. The sampling technique was consecutive sampling with 46 type 2 Diabetes Mellitus patients were selected based on inclusion criteria. Instrument used the study was a questionnaire consisted of 18 question to asses family support and 20 question to asses quality of life which was valid and reliable. Data analyses used in the study were univariate analysis to know distribution of frequency and bivariate analysis by using chi square. The result showed that p value (0,030) < alpha (0,05). It meant that there was a correlation between family support and quality of life of patients with type 2 Diabetes Mellitus in Arifin Achmad General Hospital of Riau Province. Family of the patients are expected to increase support for the patients with type 2 Diabetes Mellitus therefore it can increase quality of life of the patients with type 2 Diabetes Mellitus. Keyword: family support, type 2 Diabetes Mellitus, quality of life